Influencia del uso de las redes sociales digitales en la gestión escolar del directivo en las instituciones públicas de nivel inicial San Juan Bautista 2021 - Ramírez López, Ledis (2022)
The research was carried out in the district of San Juan Bautista, and its main objective was to explain the influence of the use of digital social networks in the school management of the director in the Public Educational Institutions of initial level in the district of San Juan Bautista in the year 2021. The type of research considered was explanatory, with a cross-sectional, field, and bivariate design. The population was made up of 28 managers, and the sample was the same census, for convenience. Two questionnaires were available for data collection, which were validated by expert judgment, and their reliability was also determined. The results show that the dimensions of online communication and information, educational community directly influence the manager's school management, so the use of online digital social networks directly and significantly influences the school management of the managers of educational institutions entry-level in the district of San Juan Bautista.